1985
DOI: 10.1002/nur.4770080213
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, perceived clinician empathy, and patient self‐disclosure

Abstract: The purpose of this study was to compare groups of outpatient hypertensive and diabetic patients to a control group (no known chronic illnesses) on their perceptions of clinician empathy and the importance and difficulty of disclosing information about themselves to health care providers. It was hypothesized that hypertensives would differ from the other groups in perceiving less clinician empathy and in attributing less importance, but greater difficulty, to self-disclosing. The sample was 54 hypertensives, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…Such responses included relief from pain, improved pulse and respiratory rates, and clients’ reports of reduced worry and anxiety. This outcome contrasts somewhat with Dawson’s (1985) report that clients with hypertension were different from other clients. Hypertensive clients perceived less empathy in clinicians, and attributed greater importance to discussing with their health care provider their responses to health care, as compared with personal problems and lifestyle matters.…”
Section: Introductioncontrasting
confidence: 81%
“…Such responses included relief from pain, improved pulse and respiratory rates, and clients’ reports of reduced worry and anxiety. This outcome contrasts somewhat with Dawson’s (1985) report that clients with hypertension were different from other clients. Hypertensive clients perceived less empathy in clinicians, and attributed greater importance to discussing with their health care provider their responses to health care, as compared with personal problems and lifestyle matters.…”
Section: Introductioncontrasting
confidence: 81%
“…This finding is congruent with outcomes reported by many other studies. For example, Dawson (1985) reported that clients with hypertension were different from other clients. They perceived less empathy in clinicians, and attributed greater importance to discussing with their health care provider their responses to health care, as compared with personal problems and lifestyle matters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scores range from -48 to +48 and a subject can complete the BLRI in 5 minutes. The BLRI has shown high levels of reliability ( r = .64 -.92) (Barrett-Lennard, 1962;Dawson, 1985;Gurman, 1977). Regarding validity, nine studies demonstrated internal reliability coefficients consistently exceeding intercorrelations among the BLRI subscales (Gurman, 1977).…”
Section: Empathy and Patient Distressmentioning
confidence: 99%